Alterações motoras e imunohistoquímica da administração crônica de propionato de testosterona em ratos, de ambos os sexos, submetidos ao modelo de parkinsonismo induzido por reserpina - Bispo, José Marcos Meneses (2016)
Parkinson's disease (PD) shows sex differences in susceptibility, pathogenesis and clinical condition. The most common incidence in males suggests sex hormones as a potential contributing factor to the individual susceptibility to this disease. Thus, the purpose of this study was evaluate the effect of chronic testosterone propionate (TP) administration on the motor and neurochemical changes in Parkinsonism model induced by reserpine (RES);and to compare the effects of administration of low doses of RES between males and females (intact and ovariectomized). A hundred ninety-two 6-9-month-old males and females Wistar rats were used. Animals were obtained from vivarium of the Department of Physiology - Federal University of Sergipe. The study was divided into three experiments: (I) testosterone propionate administration in intact male rats, (II) in intact female rats and (III) in ovariectomized rats. In all experiments, the rats were divided into eight groups: 1) testosterone propionate vehicle (CTRt) + reserpine vehicle (CTR); 2) 0.1mg / kg of TP (0.1TP) + CTR; 3) 1.0 mg / kg of TP (1.0TP) + CTR; 4) 5.0mg / kg of TP (5.0PT) + CTR; 5) CTRt + RES; 6) 0.1TP +RES; 7) 1.0TP+ RES and 8) 5.0TP + RES. Animals received 31 injections of testosterone propionate or vegetable oil (i.m.) daily and 15 injections of 0.1 mg / kg RES or vehicle (s.c.) every other day. During the treatment, the animals were weighed every four days and submitted to the following behavioral procedures: catalepsy (daily) and open field (day 31). On day 31, the rats were anesthetized, perfused and their brains were removed and subjected to the immunohistochemistry technique for tyrosine hydroxylase (TH). We show that the RES administration generates a sex-dependent response in the behavior of catalepsy and number of TH+ cells in the Ventral tegmental area (VTA). Regarding the co-administration of PT and RES in the catalepsy test, the treatment with TP showed reduced motor effects in males (Exp. I) in 5.0PT+RES group, while in females (Exp. II and III) this effect was observed at the dose of 1.0 mg / kg (1.0PT+RES) and 5.0 mg / kg (5.0PT+RES). In the open field, none of the doses of TP, in any of the experiments, was able to minimize the effects caused by the RES in motor activity. In intact males (Exp. I), all tested doses of TP were able to prevent the reduction of TH+cells caused by the RES in VTA, but not in Substantia nigra pars compacta. In intact females (Exp. II), only the dose of 5.0 mg / kg (5.0PT+RES) was able to prevent the reduction of TH+ cells in the SNpc. In ovariectomized females (Exp. III) the treatment with all doses of TP (0.1PT+RES, 1.0PT+RES and 5.0PT+RES) was able to maintain the intensity of TH in the dorsal striatum, preventing reduction caused by the RES. Taken together our results show that Chronic treatment with TP, in progressive model of parkinsonism induced by RES, showed different effects in behavioral tests and animals of different sex and conditions, showing multiple possible mechanisms of action.